Kegiatan Aktualisasi Nilai Pancasila dalam Proses Pembelajaran di Sekolah Dasar Negeri Babakan Bandung - Mariah, Salipah Jumatul; Putri, Dhea Anisa; Agni, Saharani Nurul; Bariyyah, Zulfa Hoirul; Al Mubarok, Muhammad Gufron; Mulyana, Rizki; R, Ramdani; Attibyan, Muhammad Ulwanul Umami; Dharsa, Adji Mohammad; Herdiana, Dian; Sadiah S, Siti; Kurniasih, Nani (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This article examines the importance of education in shaping students’ character through the internalization of Pancasila values, particularly the second principle, “Just and Civilized Humanity,” and the third principle, “The Unity of Indonesia.” According to Law No. 20 of 2003, education aims to develop students’ potential to possess intelligence, personality, noble character, and social skills. This study employs a qualitative method to understand the implementation of Pancasila values in a socialization activity themed “Stop Bullying and Practice Caring for Others,” conducted by students of UIN Sunan Gunung Djati Bandung on November 7, 2025, at Babakan Bandung Public Elementary School, involving classes 6A and 6B. A series of activities were carried out, including an initial survey, delivery of material on bullying, ice-breaking sessions, Q&A, and the creation of a “Tree of Emotional Expressions” as a medium to express the emotional impact of bullying. The results indicate an increased student understanding of the importance of mutual respect, empathy, and maintaining unity in social life. The implementation of Pancasila values is shown to effectively promote positive character formation while minimizing bullying behavior. This article concludes that value-based education grounded in Pancasila is highly relevant in the era of globalization, with recommendations to expand similar activities to other schools and involve families and communities to strengthen character development comprehensively.